2021
DOI: 10.1093/bjs/znab134.093
|View full text |Cite
|
Sign up to set email alerts
|

841 The psychological impact of Foundation Interim Year 1 Placements on Final Year UK Medical Students Transitioning to Foundation Year One During the COVID Era

Abstract: Introduction During the COVID pandemic, the 2019-2020 cohort of final year students were invited to participate in Foundation interim Year 1 placements (FiY1). FiY1 aimed to ease transition to Foundation Year 1 doctor (FY1). We assessed the psychological impact of FiY1 on final year medical students. Method A cross-sectional survey was distributed to final year medical students in the UK between June 4th and July 4th, 2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 7 32 The supportive environment may be why Durand-Hill et al, found that the FiY1 post led to graduates feeling less stressed and depressed. 33 Another approach to creating a supportive environment was used in Northern Ireland—termed the ‘compassionate leadership model’, where students were provided with a ‘buddy system’ and encouraged to highlight their educational needs for the FiY1 post. This approach helped students feel valued and supported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 7 32 The supportive environment may be why Durand-Hill et al, found that the FiY1 post led to graduates feeling less stressed and depressed. 33 Another approach to creating a supportive environment was used in Northern Ireland—termed the ‘compassionate leadership model’, where students were provided with a ‘buddy system’ and encouraged to highlight their educational needs for the FiY1 post. This approach helped students feel valued and supported.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to time spent with reduced exposure to the clinical setting, and increasing anxiety as they missed the benefits of this period of supported learning. 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations